ANTIMICROBIAL ACTIVITY OF FIVE SOUTH INDIAN MEDICINAL PLANTS AGAINST CLINICAL PATHOGENS - HEMA.T.A,; ARYA. A.S,; SUBHA SUSEELAN,; JOHN CELESTINAL.R.K,; DIVYA.P.V, (International Journal of Pharma and Bio Sciences, 2013)
The antimicrobial activity of leaves of five South Indian medicinal plants Adhatoda vasika, Bacopa monnieri, Carica papaya, Cissampelos pareira and Cynodon dactylon , collected from regions of Kulathoor and Malayadi were investigated against ten clinical pathogens (Bacillus subtilis, Enterobacter aerogenes, Escherichia coli, Klebsiella pneumoniae, Proteus vulgaris, Pseudomonas aeruginosa, Salmonella typhi, Shigella sp., Staphylococcus aureus and Streptococcus sp.) using agar well diffusion method and broth dilution method. The plant extracts were prepared using the solvents – acetone, ethanol and propanol. It is clear from the results that, the extract of five plants used in this study acts as a good source of antibiotics against various bacterial pathogens tested and exhibited a broad spectrum of antimicrobial activity. The phytochemical analysis revealed the presence of alkaloids in all plants selected and other secondary metabolites like tannins, glycosides and saponins were also observed in all the extracts. The MIC values ranges between 3.175µg/ml and 12.5µg/ml, whereas MBC values ranges between 6.25µg/ml and 12.5µg/ml. The results of this study support the use of all the selected five medicinal plants to discover bioactive natural products that may serve as leads in the development of new pharmaceuticals that address unmet therapeutic needs.